1989
DOI: 10.1139/z89-093
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal movements of caribou in arctic Alaska as determined by satellite

Abstract: Between 1985 and 1987, 49, 283 locations and 79, 101 sets of activity data were obtained for 34 adult female caribou of the Porcupine and Central Arctic caribou herds using satellite telemetry. Daily movement rates of female caribou from the two herds, which differ greatly in size and separation of seasonal ranges, were similar except during the spring and fall migrations. Movement rates in July exceeded those during migration in both herds. The minimum annual distance travelled by caribou cows, ranging to 505… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 0 publications
1
83
0
Order By: Relevance
“…The community is geographically isolated; it has no road access. Subsistence livelihoods depend to a great extent on the Porcupine caribou herd, for which a large research base exists (Fancy et al, 1988;Russell et al, 1992Russell et al, , 1993Griffith et al, 2002). The 1993 land-claim agreement gives the Vuntut Gwitchin First Nation substantial authority to influence the community's future.…”
Section: The Community Of Old Crow Yukon Territorymentioning
confidence: 99%
“…The community is geographically isolated; it has no road access. Subsistence livelihoods depend to a great extent on the Porcupine caribou herd, for which a large research base exists (Fancy et al, 1988;Russell et al, 1992Russell et al, , 1993Griffith et al, 2002). The 1993 land-claim agreement gives the Vuntut Gwitchin First Nation substantial authority to influence the community's future.…”
Section: The Community Of Old Crow Yukon Territorymentioning
confidence: 99%
“…Some of the longest distances traveled by extant terrestrial mammals have been reported in Alaskan caribou. Satellite tracking data suggest that herds of caribou migrate more than 2,500 km twice per year between their summer and winter habitats (20). A common factor in each of these migration patterns is that the animals return to the same place year after year, suggesting that long-distance navigation follows highly specific landmark cues also in large terrestrial animals.…”
mentioning
confidence: 99%
“…Space-use patterns of barren-ground caribou are influenced by a variety o f environmental and biological factors including whether, insect harassment, forage availability, and predation risk (Kelsall 1968, Bergerud 1996, Fancy et al 1989, Gunn et al 2002. These factors vary among caribou, making it challenging to infer the aggregate behaviour of the herd from observations of individual animals.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and movement of barren-ground caribou vary considerably by season (Fancy et al 1989, Gunn et al 2002. These dynamics influence the availability of prey (Heard and Williams 1992) and thus the reproductive success for denning wolves (Frame et al 2008).…”
Section: Distance To Caribou Migration Routesmentioning
confidence: 99%
See 1 more Smart Citation